Synthesis and Optical Properties of N-Arylnaphtho- and Anthra[2,3-d]oxazol-2-amines - Yuki Murata; Masato Kawakubo; Ayumi Maruyama; Mio Matsumura; Shuji Yasuike (Molecules)
Oxazole, a versatile and significant heteroarene, serves as a bridge between synthetic organic chemistry and applications in the medicinal, pharmaceutical, and industrial fields. Polycyclic aromatic compounds with amino groups substituted at the 2-position of an oxazole, such as 2-aminonaphthoxazoles, are expected to be functional probes, but their synthetic methods are extremely limited. Herein, we describe electrochemical reactions of 3-amino-2-naphthol or 3-amino-2-anthracenol and isothiocyanates in DMSO, using a graphite electrode as an anode and a platinum electrode as a cathode in the presence of potassium iodide (KI), which afford N-arylnaphtho- and N-arylanthra[2,3-d]oxazol-2-amines via cyclodesulfurization. This reaction is the first example of synthesis of 2-aminoxazole-based polycyclic compounds using an electrochemical reaction. An examination of the spectroscopic properties of polycyclic oxazoles revealed that the λabs value of the tetracyclic oxazoles was redshifted relative to that of the tricyclic oxazoles. Moreover, synthesized naphthalene/anthracene-fused tricyclic and tetracyclic oxazoles exhibited extended π-conjugated skeletons and fluoresced in the 340–430 nm region in chloroform.